2011
DOI: 10.1152/physiolgenomics.00199.2010
|View full text |Cite
|
Sign up to set email alerts
|

Role of the estrogen/estrogen-receptor-beta axis in the genomic response to pressure overload-induced hypertrophy

Abstract: Cardiac hypertrophy, the adaptive response of the heart to overload, is a major risk factor for heart failure and sudden death. Estrogen (E2) and estrogen receptor beta (ERbeta) offer protection against hypertrophy and in the transition to heart failure. However, the underlying pathways remain incompletely defined. We employed a publicly available microarray dataset of female wild-type (WT) and ERbeta knockout (BERKO) mice subjected to pressure overload-induced hypertrophy to perform a systematic investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 42 publications
3
50
0
1
Order By: Relevance
“…Studies in various models of acute or chronic LV injury (including chronic LV pressure overload) demonstrated antifibrotic, antihypertrophic, anti-inflammatory, antiapoptotic/prosurvival, and antioxidant effects of E2, as well as beneficial effects on mitochondrial function (11,21,28,39,42,59). Furthermore, E2 enhances nitric oxide signaling in the LV (40), and a recent study suggested that LV inotropic effects of phosphodiesterase (PDE)-5 inhibition in female rodents are estrogen-dependent (48).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in various models of acute or chronic LV injury (including chronic LV pressure overload) demonstrated antifibrotic, antihypertrophic, anti-inflammatory, antiapoptotic/prosurvival, and antioxidant effects of E2, as well as beneficial effects on mitochondrial function (11,21,28,39,42,59). Furthermore, E2 enhances nitric oxide signaling in the LV (40), and a recent study suggested that LV inotropic effects of phosphodiesterase (PDE)-5 inhibition in female rodents are estrogen-dependent (48).…”
Section: Discussionmentioning
confidence: 99%
“…Microarray data analysis. Data were analyzed as described recently (10,11) and as summarized in the Online Methods. Mouse experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Selective ERα agonism attenuates cardiac hypertrophy, increasing cardiac output, left ventricular stroke volume, and cardiac α-MyHC expression [96][97][98]. Signaling through ERβ has been studied in more depth and has been shown to counteract the development of cardiac hypertrophy by reducing the expression of hypertrophic markers, attenuating fibrosis, apoptosis and inflammation [99][100][101]. ERβ regulates a network of miRNAs, modulates p38 and ERK signaling, and affects calcineurin expression [102,103].…”
Section: Molecular Mechanisms Of Estrogen-mediated Cardio-protectionmentioning
confidence: 99%